2012
DOI: 10.4103/0974-7796.91624
|View full text |Cite
|
Sign up to set email alerts
|

Post percutaneous nephrolithotripsy nephrostomy site tuberculosis: A report of six cases

Abstract: With the increase in endoscopic surgery, there is a growing concern about the effectiveness of sterilizing reusable equipment by immersion in 2% glutaraldehyde. Although reports of port site tuberculosis (post laparoscopy) are there in the literature, those of nephrostomy site post percutaneous nephrolithotripsy are not available. We describe the clinical features and treatment of six patients who presented with biopsy-proven skin tuberculosis at the nephrostomy-site for non-healing wound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…27 Further, workup revealed a disinfectant plastic tray responsible for infections. In our study, inadequate cleaning of small-sized facial dilators (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), 18G initial puncture needle, and Amplatz sheath was probably the inciting factor for NTM outbreak. Author also recommended use of metal surface, autoclaving, or use of OPA over Glutaraldehyde to prevent infections.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…27 Further, workup revealed a disinfectant plastic tray responsible for infections. In our study, inadequate cleaning of small-sized facial dilators (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16), 18G initial puncture needle, and Amplatz sheath was probably the inciting factor for NTM outbreak. Author also recommended use of metal surface, autoclaving, or use of OPA over Glutaraldehyde to prevent infections.…”
Section: Discussionmentioning
confidence: 64%
“…8 Wound infection in PCNL is usually seen less frequently but is associated with long-term morbidity with seropurulent discharge, unsightly appearance, continuous discomfort, and taking months to get resolved ultimately. 9 Many factors have been found to be associated with these infections include the presence of external catheter such as percutaneous nephrostomy (PCN), inadequate sterilization, or high-level disinfection of the nephroscope and its accessory instruments, especially with glutaraldehyde alone. 9 PCNL procedure involves the use of an initial puncture needle, guide wires, facial dilators, nephroscope, and amplatz sheath etc., in order to reach inside the renal system accurately from flank.…”
Section: An Insight Into Outbreak Of Atypical Mycobacterial Infection...mentioning
confidence: 99%
“…6 However, port-site tuberculosis following diagnostic laparoscopy has not been reported. Ramesh et al reported eight patients with biopsy-proven tuberculosis at the port site unassociated with other clinical features of tuberculosis following cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%